Large-Scale Synthesis of 2-Chlorotetrahydroquinoline and 2-Chlorotetrahydroquinolin-8-one - Zong, Zhijian; Wu, Ke; Jin, Liqun; Sun, Nan; Hu, Baoxiang; Shen, Zhenlu; Hu, Xinquan (Synthesis, 2020)
An efficient large-scale preparation of 2-chlorotetrahydroquinoline with cyclohexanone and benzylamine as starting materials was developed and well optimized, in which benzyl-protected enamide was successfully cyclized and benzyl group was directly removed under Vilsmeier conditions. Azeotropic distillation provided 264 g of 2-chlorotetrahydroquinoline (79%) on a 2 mol scale of reaction without intermediate isolation. The downstream product 2-chlorotetrahydroquinolin-8-one was acquired through Boekelheide rearrangement, hydrolysis of acetate via NaBH4 reduction, and Anelli oxidation. With the developed procedure, the intermediates were not necessary to be isolated and 2-chlorotetrahydroquinolin-8-one was conveniently obtained with solvent slurry in 65% overall isolated yield in a four-step sequence.
Keywords: 2-chlorotetrahydroquinoline; 2-chlorotetrahydroquinolin-8-one; large-scale synthesis; enamide; cyclization; Boekelheide rearrangement